(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
In the article, the author made an analysis of the development of light industry in the Republic of Uzbekistan and studied a number of scientific works of foreign and domestic authors. Based on statistical data, the author compiled a multifactor econometric model for the development of light industry in Uzbekistan, which allowed them to identify individual patterns of the industry. Based on the correlation matrix, the relationships between the factors involved in the econometric model, as well as the private and paired relationships affecting the resulting factor, are revealed. By authors were proposed main directions of investment project management in light industry enterprises. The results of the study can be used in light industry enterprises to determine the development path.